Chronic but not acute immobilization stress stably enhances hippocampal CA1 metabotropic glutamate receptor dependent Long-Term Depression. (28th October 2016) - Sengupta, Tathagata; Das, Rishi; Chattarji, Sumantra
Highlights: Bath application of DHPG caused robust LTD in hippocampal slices from control animals. Chronic immobility stress significantly elevated this LTD when observed 24 h following the last stress event. A single stress event did not to enhance LTD, 24 h later. Abstract: Acute stress has been shown to facilitate but not increase metabotropic glutamate receptor (mGluR) mediated Long-Term Depression (LTD) in the hippocampus. However, the effect of chronic stress on mGluR dependent LTD has not been investigated. Moreover, whether stress leads to a transient modification LTD threshold or a more stable change in synaptic plasticity needs to be addressed. In the present study, we have explored the effects of both a ten-day long and a single day immobilization stress protocol on mGluR-LTD at the CA3:CA1synapse in the hippocampus of adult male Sprague-Dawley rats, a day after applying stress. Bath application of the selective group 1 mGluR agonist ( S )-3, 5-dihydroxyphenylglycine (DHPG) promoted robust LTD in hippocampal slices from control (i.e. un-stressed) animals. Administration of immobility stress for two hours per day for ten days significantly elevated this LTD to a level almost twice that of control, when observed 24 h following the last stress event. Acute stress i.e. a single day of two hours of immobilization, however, failed to significantly enhance LTD, 24 h later. These results demonstrate for the first time, that repeated exposure to stress, but not a single stress event, is required to bring about a stable alteration in mGluR mediated synaptic plasticity.